Recursos directamente recaudados y su incidencia en la ejecución presupuestal de la Municipalidad Distrital de Punchana, periodo 2020 – 2022 - Acosta Lozano, Ray Andre (2023)
The objective of the study is to Examine the Impact of Directly Collected Resources on the Budget Execution of the Municipality of Punchana during the period 2020-2022" is to analyze the origin of the income and expenses derived from the directly collected resources and their influence on the execution of the budget. In addition, it seeks to propose policies and guidelines that can improve the collection of these resources. To carry out this analysis, a quantitative and descriptive explanatory approach methodology was used. The data was obtained from the official portal of the Ministry of Economy and Finance, which provides updated and verified information about the District Municipality of Punchana. Statistical techniques were applied to obtain the results of the research and carry out its analysis. The results of the analysis indicated that, in the year 2020, the executed income amounted to S /. 482,613.00, in 2021 they were S/. 43,873.00 and in 2022 they reached S/. 1,513,033.00. Regarding expenses, S/. 1,365,519.00 in 2020, S/. 360,832.00 in 2021 and S/. 1,326,366.00 in the year 2022. In conclusion, it was determined that there is a significant relationship between the income and expenses related to the resources directly collected by the District Municipality of Punchana.